1989
DOI: 10.1039/an9891401597
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of cobalt and nickel in sea water by adsorptive cathodic stripping square-wave voltammetry

Abstract: A reliable procedure for the simultaneous determination of ultra-trace levels of cobalt and nickel in sea water is proposed, in which the complexes of cobalt and nickel with dimethylglyoxime are analysed by cathodic stripping square-wave voltammetry based on adsorptive collection at a hanging mercury drop electrode. After comparing differential-pulse cathodic stripping voltammetry with cathodic stripping square-wave voltammetry for the determination of cobalt and nickel, the latter technique was adopted becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 0 publications
2
20
0
1
Order By: Relevance
“…Often, CSV techniques involve complexation of the metal ions of interest, and the use of a hanging mercury drop electrode (HME). Zhang et al [4] reported the analysis of cobalt and nickel from seawater as dimethylglyoxime (DMG) complexes at an HME, and Zhang and Millero [5] analyzed a range of metal ions, including Pb 2 , as sul®de complexes. Cathodic stripping voltammetry methods for directly analyzing aqueous lead have also been developed previously.…”
Section: Introductionmentioning
confidence: 99%
“…Often, CSV techniques involve complexation of the metal ions of interest, and the use of a hanging mercury drop electrode (HME). Zhang et al [4] reported the analysis of cobalt and nickel from seawater as dimethylglyoxime (DMG) complexes at an HME, and Zhang and Millero [5] analyzed a range of metal ions, including Pb 2 , as sul®de complexes. Cathodic stripping voltammetry methods for directly analyzing aqueous lead have also been developed previously.…”
Section: Introductionmentioning
confidence: 99%
“…As curvas analíticas foram lineares para 0,1 ng mL -1 , para os dois metais. A utilização da técnica adsortiva de redissolução com varredura catódica em voltametria de onda quadrada, para a determinação simultânea de Co e Ni em água do mar foi descrita por Zhang et al 37 . O pH das amostras foi controlado, com tampão amônia/trietanolamina (pH=8,0), o complexante utilizado foi DMG.…”
Section: Cromatografiaunclassified
“…Although some of the CSV techniques for lead detection involve complexation and/or the use of a hanging mercury drop electrodes, 21,22 there are also a significant number of reports of successful CSV analysis of lead at various solid electrode substrates. 3,[23][24][25][26][27][28] Classical "nobel" metal electrodes 25 and glassy carbon electrodes 20 can sometimes be limited in terms of sensitivity by surface oxidation and reduction processes, and the amount of Pb 2+ deposited from solution as lead dioxide is often restricted in these cases due to the proximity of solvent decomposition to the cathodic stripping peak of PbO2.…”
Section: Introductionmentioning
confidence: 99%